THE ROLE OF PEDAGOGICAL CONTROL IN CHANGING APPROACHES TO LEARNING - Daria A. Rusanova (Высшее образование в России)
The problem of forming students’ attitude to learning and the teacher’s role in this process is considered in the article. It examines how pedagogical assessment influences on the formation of the positive motivation to learning and creation reflexive assessmentconditions. Recommendations on involvement students in the assessment activities aimed at the developing the self- and mutual assessment skills are given.